2019
DOI: 10.1001/jamanetworkopen.2019.5967
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Total Usual Dietary Intakes of Pregnant Women in the United States

Abstract: Key Points Question How do the usual dietary intakes of pregnant US women compare with the National Academies of Science, Engineering, and Medicine Dietary Reference Intakes for nutritional adequacy and excess? Findings This cross-sectional analysis of 1003 pregnant US women found that many pregnant women did not consume enough key nutrients during pregnancy, specifically, vitamins A, C, D, E, K, and B 6 , as well as folate, choli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
145
3
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(177 citation statements)
references
References 59 publications
(132 reference statements)
13
145
3
9
Order By: Relevance
“…The rates of deficiency for vitamins B6 and B12 are not well documented, however the role of vitamin B9 (folate) in fetal development continues to be one the most well-studied of all nutrients during pregnancy [9,[66][67][68][69][70]. An analysis of NHANES 2001-2014 data of pregnant women found mean intakes of vitamin B6, folate, and vitamin B12 from food averaged near the EAR, and intake from food and supplements averaged at least double the EAR [71].…”
Section: B-vitaminsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rates of deficiency for vitamins B6 and B12 are not well documented, however the role of vitamin B9 (folate) in fetal development continues to be one the most well-studied of all nutrients during pregnancy [9,[66][67][68][69][70]. An analysis of NHANES 2001-2014 data of pregnant women found mean intakes of vitamin B6, folate, and vitamin B12 from food averaged near the EAR, and intake from food and supplements averaged at least double the EAR [71].…”
Section: B-vitaminsmentioning
confidence: 99%
“…Recent data suggest the rate of folate deficiency in pregnancy in the United States is as low as 0.5%, since mandatory grain fortification started in 1998 [72], dramatically reducing the number of birth defects, especially spina bifida [66]. Bailey, et al, (2019) found folate intakes from both food and supplements were at risk of inadequate intake, with 16.4% of pregnant women below the EAR, however, at the same time, 33.4% of pregnant women had intakes above the Tolerable Upper Intake Level (UL) [71]. This wide disparity in intakes suggests a folate source that is not consistent across the population, potentially from inconsistent prenatal vitamin use by expectant mothers [71].…”
Section: B-vitaminsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal anemia might cause serious fetal and maternal complications during pregnancy (7). The effects of this disorder on the placenta and child weight have been reported in the several studies (8)(9)(10)(11). Anemia with hemoglobin levels between 6-10 g/dL might cause placental hypertrophy during the pregnancy.…”
mentioning
confidence: 97%
“…The maternal microbiome is identified as a therapeutic target to improve the health of pregnant women and their offspring that is widely understudied 29,30 . The current dietary fiber intake in the US during pregnancy is low, 17.3 g/day 31 , which is well below the recommended intake of 28 g/day 32 . Therefore, increasing fiber intake during pregnancy has the potential to have a large and beneficial impact.…”
mentioning
confidence: 83%